Intermolecular insights into allosteric inhibition of histone lysine-specific demethylase 1 - Zhang, Xiangyu; Sun, Yixiang; Zhang, Ziheng; Wang, Hanxun; Wang, Jian; Zhao, Dongmei (Biochimica et biophysica acta. General subjects, 2021)
Histone lysine-specific demethylase 1 (LSD1) has become a potential anticancer target for the novel drug discovery. Recent reports have shown that SP2509 and its derivatives strongly inhibit LSD1 as allosteric inhibitors. However, the binding mechanism of these allosteric inhibitors in the allosteric site of LSD1 is not known yet. The stability and binding mechanism of allosteric inhibitors in the binding site of LSD1 were evaluated by molecular docking, ligand-based pharmacophore, molecular dynamics (MD) simulations, molecular mechanics generalized born surface area (MM/GBSA) analysis, quantum mechanics/molecular mechanics (QM/MM) calculation and Hirshfeld surface analysis. The conformational geometry and the intermolecular interactions of allosteric inhibitors showed high binding affinity towards allosteric site of LSD1 with the neighboring amino acids (Gly358, Cys360, Leu362, Asp375 and Glu379). Meanwhile, MD simulations and MM/GBSA analysis were performed on selected allosteric inhibitors in complex with LSD1 protein, which confirmed the high stability and binding affinity of these inhibitors in the allosteric site of LSD1. The simulation results revealed the crucial factors accounting for allosteric inhibitors of LSD1, including different protein–ligand interactions, the positions and conformations of key residues, and the ligands flexibilities. Meanwhile, a halogen bond interaction between chlorine atom of ligand and key residues Trp531 and His532 was recurrent in our analysis confirming its importance. Overall, our research analyzed in depth the binding modes of allosteric inhibitors with LSD1 and could provide useful information for the design of novel allosteric inhibitors. [Display omitted] •The stability and binding mechanism of allosteric inhibitors in the binding site of LSD1 were estimated by molecular docking and pharmacophore.•Based on the QM/MM optimization, intermolecular interactions of selected complexes were analyzed by hirshfeld surfaces.•An interaction model inside the LSD1 allosteric site was proposed to provide guidance for designing LSD1 inhibitors.